Laboratorio para el estudio de bombas centrífugas para la universidad Antonio Nariño sede Cúcuta - Moncada Rubio, Yesid Gerardo (Universidad Antonio Nariño, 2021)
This project began with the purpose of implementing a laboratory in didactic cuts for the study and research of centrifugal pumps based on a real prototype, for which the cuts were designed and elaborated didactics to the pump with the help of specialized tools, for the internal visualization of the components, identified with colors; Strategic didactic cuts were made to this to show internal components and thus better understand their internal functioning, the metal support that will carry the centrifugal pump was also built with the help of the metalworking sector, therefore, the laboratories of the Antonio Nariño University will be provided so that the students better understand the study of the centrifugal pump component that relates what is seen in the classrooms.